PENGARUH LINGKUNGAN KELUARGA DAN EFIKASI DIRI TERHADAP MINAT BERWIRAUSAHA MAHASIWA PROGRAM STUDI S1 MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS RIAU” - ,Kurniawaty Fitri, Mira Santika ,Arwinence Pramadewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The purpose of this study is to ascertain how self-efficacy and the family environment affect entrepreneurial interests in management study program students in the 2020–2022 batch at the University of Riau's Faculty of Economics and Business. With a sample size of ninety, the population of this study comprised all students majoring in management in the class of 2020–2022, Faculty of Economics and Business, University of Riau. In this work, multiple linear regression analysis was combined with a quantitative descriptive technique. 1. The family environment has a positive and significant influence on the interest in entrepreneurship, according to the data. 2. The desire in entrepreneurship is positively and significantly influenced by one's job self-efficacy.” Keywords: Family environment, self-efficiency and interest in entrepreneurship